2009
DOI: 10.1128/jb.01526-08
|View full text |Cite
|
Sign up to set email alerts
|

Two Redundant Sodium-Driven Stator Motor Proteins Are Involved in Aeromonas hydrophila Polar Flagellum Rotation

Abstract: Motility is an essential characteristic for mesophilic Aeromonas strains. We identified a new polar flagellum region (region 6) in the A. hydrophila AH-3 (serotype O34) chromosome that contained two additional polar stator genes, named pomA 2 and pomB 2. A. hydrophila PomA 2 and PomB 2 are highly homologous to other sodium-conducting polar flagellum stator motors as well as to the previously described A. hydrophila AH-3 PomA and PomB. pomAB and pomA 2 B 2 were present in all the mesophilic Aeromonas strains te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 51 publications
(66 reference statements)
0
39
0
3
Order By: Relevance
“…B. subtilis MotAB and S. oneidensis MotAB-MotXY are proton-driven, whereas B. subtilis MotPS and S. oneidensis PomAB-MotXY are sodium-driven. In contrast, both A. hydrophila polar flagellum stator complexes are sodium-driven, although they have different sensitivities to sodium variations (Wilhelms et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…B. subtilis MotAB and S. oneidensis MotAB-MotXY are proton-driven, whereas B. subtilis MotPS and S. oneidensis PomAB-MotXY are sodium-driven. In contrast, both A. hydrophila polar flagellum stator complexes are sodium-driven, although they have different sensitivities to sodium variations (Wilhelms et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we demonstrated that A. hydrophila has two redundant sodium-dependent polar stators, PomAB and PomA 2 B 2 , which allow bacteria to swim in liquid medium and soft agar (Wilhelms et al, 2009). Since both polar flagellum stators are sodium-dependent, and subunits PomA/PomA 2 and PomB/PomB 2 are homologous proteins, they might constitute functional natural hybrid motors.…”
Section: A Hydrophila Hybrid Polar Flagellum Stators Are Not Functionalmentioning
confidence: 99%
See 3 more Smart Citations